2016
DOI: 10.1002/cne.23998
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic organization of striate cortex projections in the tree shrew: A comparison of the claustrum and dorsal thalamus

Abstract: The tree shrew (Tupaia belangeri) striate cortex is reciprocally connected with the dorsal lateral geniculate nucleus (dLGN), the ventral pulvinar nucleus (Pv), and the claustrum. In the Pv and dLGN, striate cortex projections are thought to either strongly “drive”, or more subtly “modulate” activity patterns respectively. To provide clues to the function of the claustrum, we compared the synaptic arrangements of striate cortex projections to the dLGN, Pv and claustrum using anterograde tracing and electron mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 73 publications
(133 reference statements)
1
22
0
Order By: Relevance
“…The terminals that arise from layer V cells are significantly larger than corticogeniculate terminals or tectopulvinar terminals (rat; Bourassa and Deschênes, 1995; tree shrew; Chomsung et al, 2008; Day-Brown et al, 2016; cat; Guillery et al, 2001; Huppé-Gourgues et al, 2006; Kelly et al, 2003; rat; Li et al, 2003c; Masterson et al, 2009), and similar large V1 corticopulvinar terminals are found in the mouse (Figure 5A, 7A). …”
Section: The Striate-recipient Zones Of the Pulvinarmentioning
confidence: 63%
“…The terminals that arise from layer V cells are significantly larger than corticogeniculate terminals or tectopulvinar terminals (rat; Bourassa and Deschênes, 1995; tree shrew; Chomsung et al, 2008; Day-Brown et al, 2016; cat; Guillery et al, 2001; Huppé-Gourgues et al, 2006; Kelly et al, 2003; rat; Li et al, 2003c; Masterson et al, 2009), and similar large V1 corticopulvinar terminals are found in the mouse (Figure 5A, 7A). …”
Section: The Striate-recipient Zones Of the Pulvinarmentioning
confidence: 63%
“…boutons that extend off the axon (da Costa et al, 2010;Smith et al, 2017), which is consistent with "modulator" type synapses that exhibit paired-pulse facilitation on their postsynaptic targets (Sherman & Guillery, 1998). However, there is some controversy surrounding the "driver/modulator" categorization for claustral synapses, especially for corticoclaustral synapses Day-Brown et al, 2017).…”
Section: Laminar Organization Of Connectivity Between Cla-den and Cmentioning
confidence: 68%
“…As shown in the photomicrograph in Figure d, these terminals appear as small (<0.5 μm diameter), “mushroom‐like” boutons that extend off the axon (da Costa et al, ; Smith et al, ), which is consistent with “modulator” type synapses that exhibit paired‐pulse facilitation on their postsynaptic targets (Sherman & Guillery, ). However, there is some controversy surrounding the “driver/modulator” categorization for claustral synapses, especially for corticoclaustral synapses (Brown et al, ; Day‐Brown et al, ). Specifically, these authors measured the size of corticoclaustral synapses (0.34 ± 0.02 μm 2 ) and compared them to the size of corticothalamic modulators (0.24 ± 0.01 μm 2 ) and corticothalamic drivers (0.94 ± 0.08 μm 2 ).…”
Section: Reassessing the Relationship Of The Cla And En In Rodentsmentioning
confidence: 99%
“…In tree shrews, projections from the striate cortex to the extrageniculate thalamus are limited to the ventral pulvinar nucleus and lateral intermediate nucleus (Huerta et al 1985;Day-Brown et al 2007), and, as demonstrated in the current study, only the temporal cortex projects to the Pd and Pc. In contrast, the tectorecipient zones of the primate pulvinar nucleus receive extensive input from both the striate and temporal cortex (Glendenning et al 1975;Symonds and Kaas 1978;Lin and Kaas 1979;Diamond 1980, 1981;Wall et al 1982;Ungerleider et al 1983).…”
Section: Relation To Primate Pulvinocortical Connectionssupporting
confidence: 74%